1997
DOI: 10.3386/w6049
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Theory of GATT

Abstract: GxCCCq pin bi&tbpa ui&A pc dnciicq mjiponi cxbjcu bcurn22!ou hLoArqcq tp tjijj CLQqJt © T ÔO P> IC)1C B9MC11 &uq jçopci 8W! VII L!jJLcacLAcq JOI4 2CCTOU2 oi TCXC uo o &ntpot uq not tpoac OL wc jqou&j flflLC&I1 o. peonounc KC2LCW LG2C9tC bLOEL&UJ ! jutcu&pou&j jpqc &uq pmcaucuç vuA obiuioua cxbtcaacq &LG wo oflJG IJUSUC!&J aflbbOT4 b1014qCq P? IPG 14ST!0U&I 2C!©UtC 01mq&I0U LP!a L&bCL ! L&14 °J. J4J{2 EJJ°' T W9 CCU{GL OL yqmccq wqX !U {JJG Bcpat1!oLI cicuccw 3faJcL !2 ujao flfGIJq OL b&gicjlrnna wtu4oiq flULAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
647
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(660 citation statements)
references
References 0 publications
7
647
1
5
Order By: Relevance
“…Reciprocity and conditionality are central to theoretical studies on trade agreements (Bagwell and Staiger, 1999;2011). Bagwell and Staiger (2011) point out that developing countries can only benefits from trade agreements if they do not simply "free ride" on reciprocal MFN concessions between developed countries, but liberalize in turn.…”
Section: Related Literaturementioning
confidence: 99%
“…Reciprocity and conditionality are central to theoretical studies on trade agreements (Bagwell and Staiger, 1999;2011). Bagwell and Staiger (2011) point out that developing countries can only benefits from trade agreements if they do not simply "free ride" on reciprocal MFN concessions between developed countries, but liberalize in turn.…”
Section: Related Literaturementioning
confidence: 99%
“…The dispute settlement system forms the central mechanism to enforce international trade law and embodies a high level of legalization in comparison with other international institutions. It has attracted wide attention from scholars in political science, economics, and law (e.g., Bagwell and Staiger 1999;Bown 2004b;Busch 2000;Guzman and Simmons 2002;Jackson 1997;Maggi 1999;Reinhardt 2001;Rosendorff 2005). While research has found no evidence of any bias in rulings against developing countries (Busch and Reinhardt 2003;Moon 2006), weak enforcement could arise through an earlier selection effect if developing countries do not file complaints to challenge violations.…”
mentioning
confidence: 99%
“…Like Bagwell and Staiger (1999) and (2001), we investigate the ef…ciency rationale behind WTO's principles. However, they emphasize reciprocity in market access in a perfectly competitive economy where externalities between countries are limited to world price e¤ects.…”
Section: Introductionmentioning
confidence: 99%